2015
DOI: 10.1007/s00122-015-2504-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DArT and SNP scan for QTL associated with resistance to stripe rust (Puccinia striiformis f. sp. tritici) in elite ICARDA wheat (Triticum aestivum L.) germplasm

Abstract: Identified DArT and SNP markers including a first reported QTL on 3AS, validated large effect APR on 3BS. The different genes can be used to incorporate stripe resistance in cultivated varieties. Stripe rust [yellow rust, caused by Puccinia striiformis f. sp. tritici (Pst)] is a serious disease in wheat (Triticum aestivum). This study employed genome-wide association mapping (GWAM) to identify markers linked to stripe rust resistance genes using Diversity Arrays Technology (DArT(®)) and single-nucleotide polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 97 publications
6
45
1
Order By: Relevance
“…Genome-wide association studies (GWAS) provide dense genome coverage and allow for accurate identification of putative QTL in unstructured populations (Lorenz et al 2011). It has been routinely used to identify the genetic basis of simple and complexly inherited agronomic and adaptive traits (Jighly et al 2015; McCouch et al 2016; Sun et al 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) provide dense genome coverage and allow for accurate identification of putative QTL in unstructured populations (Lorenz et al 2011). It has been routinely used to identify the genetic basis of simple and complexly inherited agronomic and adaptive traits (Jighly et al 2015; McCouch et al 2016; Sun et al 2017). …”
Section: Introductionmentioning
confidence: 99%
“…In addition to Yr2, we also postulated the presence of an additional unknown resistance gene or genes in these lines. Several minor-and major-effect stripe rust resistance genes have been introduced from wheat relatives and alien species for control of the disease ( Jighly et al, 2015;Maccaferri et al, 2015;Rosewarne et al, 2013). Additionally, the crossing and backrossing of these wheat-alien introgression lines to each other resulted in the pyramiding of resistance genes, leading to lines containing a combination of at least two or three Yr resistance genes (Forsström and Merker, 2001;Merker, 1984;Merker and Lantai, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…To avoid contamination among Pst isolates, inoculated plants were individually covered with cellophane bags prior to sporulation (Sørensen et al, 2016) and then the Pst spores were harvested three or four times from 16 to 20 d after inoculation. The protocols used for assessing the resistance of seedling plants at Izmir were according to Jighly et al (2015). For ease of handling, each set of 34 pots (7 by 7 by 8 cm), including one susceptible control (Morocco or Cartago), was placed in a plastic tray.…”
Section: Seedling Resistance Specificity Towards Multiple Isolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Yrq2 was mapped on chromosome 3AS in wheat line Xichang 76-9 but confers slow rusting , and therefore should be different from YrTye. Through genome-wide association mapping, Jighly et al (2015) reported a QTL on 3AS to confer seedling resistance, but neither the gene nor its location has been validated. Because of no any formally named Yr gene was previously located on chromosome 3AS (McIntosh et al 2014), we named YrTye as Yr76.…”
Section: Discussionmentioning
confidence: 99%